To eat or not to eat . : or relationships of art with food in the 20th century. - Alba Rico, Santiago; Barrero, Manuela; Bonet, Eugeni; Castro Flórez, Fernando; Corbeira, Dario; Costa, Juan Manuel; Díez, Celia; Felipe, Francisco; Garcia Olmedo, Francisco; Golay, Christophe; Haacke, Hans; Hartung, Elisabeth; et al. (Salamanca : Consorcio Salamanca, 2003)
Adams, China ; Alhäuser, Sonja ; Antoni, Janine ; Baldessari, John ; Baluschek, Hans ; Benner, Ron ; Beuys, Joseph ; Billingham, Richard ; Blume, Anna & Bernhard Johannes ; Brecht, George ; Broodthaers, Marcel ; Brossa, Joan ; Brus, Günter ; Chicago, Judy ; Dali, Salvador ; Delvoye, Wim ; Depero, Fortunato ; Dominguez, Oscar ; Duchamp, Marcel ; Estampa Popular ; Evans, Walker ; Fabro, Luciano ; Fernandez, Luis ; Fritsch, Katharina ; General Idea ; Goldin, Nan ; Gonzalez-Torres, Felix ; Gordillo, Luis ; Gormley, Antony ; Graham, Dan ; Grippo, Victor ; Gris, Juan ; Grosz, George ; Guttuso, Renato ; Haacke, Hans ; Hamilton, Richard ; Hatoum, Mona ; Heartfield, John ; Herold, Georg ; Hidalgo, Juan ; Hirst, Damien ; Höfer, Candida ; Jaar, Alfredo ; Jiménez Espinosa, Agustin ; Kabakov, Ilya ; Kentridge, William ; De Keyzer, Carl ; Kollwitz, Kathe ; Kosuth, Joseph ; Lanzarini, Ricardo ; Levine, Les ; Lex-Nerlinger, Alice ; Lopez, Antonio ; Lucas, Sarah ; Mamedov, Raoef ; Manzoni, Piero ; Margolles, Teresa ; Martinez, César ; Matta-Clark, Gordon ; Goodden, Caroline ; Landry, Richard ; Savage, Cosmos ; Kushner, Robert ; McCarthy, Paul ; Melendez, Luis ; Miralda, Antoni ; Miro, Joan ; Mühl, Otto ; Muniz, Vik ; Muntadas, Antoni ; Nannucci, Maurizio ; Nauman, Bruce ; Neto, Ernesto ; Nitsch, Hermann ; Oppenheim, Meret ; Parker, Cornelia ; Penone, Giuseppe ; Pérez-Quiroga, Ana ; Pierson, Jack ; Man Ray ; Rhoades, Jason ; Rodchenko, Alexander ; Romero de Torres, Julio ; Rosler, Martha ; Roth, Dieter ; Sandoval, Rosemberg ; Sarmiento, José Antonio ; Schwarzkogler, Rudolf ; Schulze, Andreas ; Severini, Gino ; Sierra, Santiago ; Simpson, Lorna ; Skoglund, Sandy ; Sougez, Emmanuel ; Spitzer, Serge ; Spoerri, Daniel ; Staeck, Klaus ; Taylor-Wood, Sam ; etc.
Comer o no Comer = To Eat or not to Eat, CASA (Centro de Arte de Salamanca), Salamanca, 2002-11-23. 2003-01-19
boek